Effectiveness of biological control of Phytophthora capsici in pepper by Trichoderma asperellum strain T34 - SEGARRA, Guillem; AVILÉS, Manuel; CASANOVA, Eva; BORRERO, Celia; TRILLAS, Isabel (Phytopathologia Mediterranea, 2012)
Pepper (Capsicum annuum L.), one of the most widely grown vegetables worldwide, is susceptible to root rot caused by Phytophthora capsici. Many biocides have recently been banned in Europe because of human health and environmental concerns. Integrated pest management is a European priority, where biological control together with other agronomic practices should replace pesticide management of plant diseases in the future. Application of different concentrations of the fungus Trichoderma asperellum strain T34 (the in T34 Biocontrol®) on incidence of disease caused by P. capsici in pepper was studied. Different methods of application of the microbial control agent and inoculation of the pathogen were examined. T34 and etridiazole (Terrazole®) were compared for their ability to suppress P. capsici. T34 reduced disease in most of the assayed situations (up to 71% disease reduction), while etridiazole was effective only when applied at the same time as the pathogen. The results obtained are discussed on the basis of the different modes of action of T34 and etridiazole. T34 is a useful biological alternative to chemicals for the control of P. capsici in pepper.